2013
DOI: 10.1111/jcpt.12118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CYP1A2 polymorphism on the pharmacokinetics of agomelatine in Chinese healthy male volunteers

Abstract: The rs762551 A, rs2470890 T and rs2472304 A genotype presented a significantly lower level of agomelatine exposure (AUC, Cmax ) compared with the rs762551 C, rs2470890 C and rs2472304 G genotype in Chinese healthy subjects. It suggested that the rs762551, rs2470890 and rs2472304 genetic polymorphism might be associated with the marked interindividual variability of agomelatine, and the pharmacokinetic profile of agomelatine may be different in different races.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 21 publications
4
24
3
Order By: Relevance
“…The agomelatine pharmacokinetic parameters that we obtained were different from those found in other bioequivalence trial conducted in healthy Chinese subjects (8). It has been previously stated that agomelatine pharmacokinetic profile could be different among races (10), which was also shown in our study as Caucasians showed an approximately 50% less AUC compared to Latin, however, no association was found after correction for the studied genotypes. Thus, these apparently marked differences were due to the different CYP1A2 genotype distribution among the two groups.…”
Section: Agomelatine Pharmacokineticscontrasting
confidence: 95%
See 1 more Smart Citation
“…The agomelatine pharmacokinetic parameters that we obtained were different from those found in other bioequivalence trial conducted in healthy Chinese subjects (8). It has been previously stated that agomelatine pharmacokinetic profile could be different among races (10), which was also shown in our study as Caucasians showed an approximately 50% less AUC compared to Latin, however, no association was found after correction for the studied genotypes. Thus, these apparently marked differences were due to the different CYP1A2 genotype distribution among the two groups.…”
Section: Agomelatine Pharmacokineticscontrasting
confidence: 95%
“…Not only polymorphisms in CYP1A2 and ABCB1 have been previously associated with the noticeable interindividual variability of agomelatine, but also its pharmacokinetic profile could be different among races (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, the CYP1A2 gene is highly inducible by many environmental factors, and functional polymorphisms have mostly been described in Asian populations (15). The two CYP1A2 variants that fulfilled our criterion of an MAF of greater than 0.05 in Caucasians (CYP1A2*1C and CYP1A2*1F) were not included in the study because of the limited evidence that they have a significant influence on RPV pharmacokinetics (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Several CYP1A2 single nucleotide polymorphism (SNPs, such as srs762551, rs2470890, and rs2472304) have been reported to be involved in the marked variability in metabolism and drug concentrations. 13) This may also provide an explanation to the different pharmacokinetic profiles in different races. Agomelatine is extensively distributed throughout the body, which might also result in high inter-individual variability.…”
Section: )mentioning
confidence: 99%
“…11) Song et al have demonstrated that a genetic polymorphism of CYP1A2 is associated with the marked inter-individual variation in agomelatine metabolism. 13) Besides, the ingestion of high-fat food does not alter the absorption or the bioavailability of agomelatine. 11) To apply for marketing of a generic agomelatine formulation produced by Jinan Limin Pharmaceutical Co., Ltd., a bioequivalence study is required after approval for the clinical trial by the Chinese Food and Drug Administration (CFDA).…”
mentioning
confidence: 99%